KECURANGAN AKADEMIK PADA MAHASISWA AKUNTANSI BERDASARKAN PERSPEKTIF FRAUD DIAMOND - Billy Billy; Andrianus Andrianus; Retno Yuliati; Yang Elvi Adelina (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2019)
The purpose of this research is to examine which factors that drive students especially that majoring in accounting, commit academic dishonesty based on fraud diamond theory and refers to (Sabli, Hamid, Haron, & Wahab, 2018) research. Based on all initial research, we can see that there are many inconsistent results from many universities. The sampling method that we use for this research is purposive sampling using questionnaires. The object of this research is Undergraduate Accounting Student from one of the Public University in Tangerang (XYZ) from the second to the eighth semester (2015-2018 batch), within the total of 260 respondents. Those data samples are processed with Structural Equation Model (SEM). The result of this research shows that only rationalization has positive significant correlation to academic dishonesty. The model of this research is proven to fulfill the goodness-of-fit, unidimensionality, and reliability standard. The result is adequate to provide input about the importance of maintaining integrity, especially because most of these students will become an accountant in the future. Keywords: Fraud diamond, academic dishonesty, accounting student